PERANCANGAN BUKU POP-UP MONUMEN CAGAR BUDAYA DI SURABAYA DENGAN TEKNIK BOX AND CYLINDER SEBAGAI UPAYA PENGENALAN SEJARAH TERHADAP ANAK SEKOLAH DASAR - Putra Ary, Fahmy Dwika; Martono, Siswo; Yuan, Dhika (Jurnal Art Nouveau, 2017)
The book is a print media that plays a role to provide educational information to all circles of society, pop-up books are books that contain an interactive element when opened and as if there is an object or object that emerged from a pop-up book that provides a visualization of Yang Interesting. In the design of this pop-up book will discuss about the cultural heritage monument located in the city of Surabaya are still many children who do not know the story behind the history of the monument.With the design of the pop-up book of monuments in Surabaya it aims to introduce the history that is on the monument in Surabaya in the form of a pop-up book. By doing research approach to be more focused, hence this research use qualitative research method through collecting data obtained from interview, observation and documentation. Given the lack of books that inform or introduce history on the monument in Surabaya.Using pop-up books, box and cylinder techniques and v-folding support techniques can be mutually informational and read-like for children and can increase reading interest.Keywords: Designing, Pop-Up Book, Cultural Heritage Monument, Surabaya City, Box and Cylinder Technique, History Introduction, Primary School Children.